Perinatal Factors Associated With Mental Health Problems Among Postnatal Women Referred to the University Psychiatry Unit, National Hospital of Sri Lanka - Amanda Kasturi Mudali; Chathurie Suraweera; TVM Pieris; MRIF Ariyachandra; AGUS Gunathilaka (BJPsych Open)
Aims: The postpartum period exerts a profound influence on maternal mental health. This study aimed to describe mental health problems and identify associated perinatal factors in women referred to the University Psychiatry Unit, National Hospital of Sri Lanka (NHSL) during the postnatal period.